Effect of Urea and SP-36 on the Growth of Grafted Rubber Seedling (Hevea brasiliensis Muell.Arg.) Clone PB 260 - Fredrikus Ding Ding; Helda Syahfari; Marisi Napitupulu (Universitas 17 Agustus 1945 Samarinda, 2019)
This study was conducted from February s / d May at the Institute for Agriculture and Technology (BPTP) East Kalimantan, this study aims to look at the different types of growing medium and the addition of TSP fertilizer in cultivation of oyster mushroom (Pleurotas astreatus) [Jacq FR] Kummer) .This research used Completely Randomized Design (CRD) factorial with two factors, factor 1: type of planting medium consisting of 2 treatment levels, namely (1. Straw Rice, 2. Powder Saws), 2: Type of fertilizer treatments consisting of 1 level namely (1. controls, 2. TSP 0.2%, 3. TSP 0.4%, 4. TSP 0.6%). Each treatment loaded with 5 replicates the data obtained were analyzed with ANOVA and if significant then further tested by using Duncan C DMRT at 95% confidence level, while the relationship between the effect of concentration (treatment) with the observed parameters analyzed with regression Simple linear. Parameters measured were emerging mycelium first time (hst), mycelium meets media (HST) initial appearance of the fruiting bodies (hst), the time of harvest, the number of fruiting bodies, hoods maximum width, stem length fruiting bodies, and the weight of the fruit.Results indicate that the rice straw media with TSP fertilizer as much as 0.6% on average produce mycelium formed fastest time is 3 DAT (Days After Planting, average fruit weight of 103.74 grams.Compared with sawdust medium with fertilizer TSP as much as 0.6% on average produce mycelium formed fastest time is 7 HST average body weight of 105.64 grams of fruit.Conclusions obtained from the results of the study showed that the rice straw media faster than the appearance of mycelium on sawdust media. But for a number of shoots on media more than the media sawdust rice straw.